THE IMPACT OF CHATGPT-BASED ASSISTANCES ON COMPUTER SCIENCE STUDENTS’ LEARNING - Erkiniy, Yulduz; Bobojonova , Shakhzoda (Innovative Development in Educational Activities, 2023)
This article explores the impact of ChatGPT-based virtual assistants on computer science students’ learning experiences. By enabling interactive conversations and providing instant explanations, these AI-powered assistants enhance understanding, promote problem-solving skills, and offer support in coding challenges. The article discusses both the positive and negative impacts of integrating ChatGPT-based assistants into computer science education.